Structural and chemical biology of deacetylases for carbohydrates, proteins, small molecules and histones - Bürger, Marco (Commun Biol, 2018)
Deacetylation is the removal of an acetyl group and occurs on a plethora of targets and for a wide range of biological reasons. Several pathogens deacetylate their surface carbohydrates to evade immune response or to support biofilm formation. Furthermore, dynamic acetylation/deacetylation cycles govern processes from chromatin remodeling to posttranslational modifications that compete with phosphorylation. Acetylation usually occurs on nitrogen and oxygen atoms and are referred to as N- and O-acetylation, respectively. This review discusses the structural prerequisites that enzymes must have to catalyze the deacetylation reaction, and how they adapted by formation of specific substrate and metal binding sites.